Studi Literatur Analisis terhadap Perilaku Menyimpang di Kalangan Remaja - Dery Zelviro Ronanda; Dian Nawang Sari; Elsa Dwi Amanda Tanjung; Hera Wati; Julia Istikhomah; Laila Sabrina; Putri Defmawita; Putri Nurul Parhana; Rizki Nur Alifah; Romodona Romodona (Nirta Learning Centre, 2024)
This research analyzes deviant behavior among adolescents, which is often triggered by the search for self-identity during the transition period between childhood and adulthood. Physical, psychological and social changes make teenagers vulnerable to the influence of peers, social media and the environment, which can lead to behavior such as alcohol abuse, drugs, brawls, online gambling and promiscuity. The method used is library research, namely literature review (library research). The purpose of this research is to provide readers with an understanding of deviant behavior that is usually carried out by teenagers, which reveals that deviant behavior not only affects individuals, but also families and society. This research is a literature study that raises the problem.